Dietary Polyphenols, Plant Metabolites, and Allergic Disorders: A Comprehensive Review - Mohd Farhan; Asim Rizvi; Mohammad Aatif; Ghazala Muteeb; Kimy Khan; Farhan Asif Siddiqui (MDPI AG, 2024)
Given the ongoing rise in the occurrence of allergic disorders, alterations in dietary patterns have been proposed as a possible factor contributing to the emergence and progression of these conditions. Currently, there is a significant focus on the development of dietary therapies that utilize natural compounds possessing anti-allergy properties. Dietary polyphenols and plant metabolites have been intensively researched due to their well-documented anti-inflammatory, antioxidant, and immunomodulatory characteristics, making them one of the most prominent natural bioactive chemicals. This study seeks to discuss the in-depth mechanisms by which these molecules may exert anti-allergic effects, namely through their capacity to diminish the allergenicity of proteins, modulate immune responses, and modify the composition of the gut microbiota. However, further investigation is required to fully understand these effects. This paper examines the existing evidence from experimental and clinical studies that supports the idea that different polyphenols, such as catechins, resveratrol, curcumin, quercetin, and others, can reduce allergic inflammation, relieve symptoms of food allergy, asthma, atopic dermatitis, and allergic rhinitis, and prevent the progression of the allergic immune response. In summary, dietary polyphenols and plant metabolites possess significant anti-allergic properties and can be utilized for developing both preventative and therapeutic strategies for targeting allergic conditions. The paper also discusses the constraints in investigating and broad usage of polyphenols, as well as potential avenues for future research.